Pears cultivars, production and harvesting - Alberto Ramos L.* (2019)
© 2019 by Nova Science Publishers, Inc.This book brings up-to-date information on different topics about the pear tree cultivation. The book was organized by Alberto Ramos Luz, Technologist in Fruit Crops, MD and PhD in Plant Production, specialist and lover of this culture. The chapters were written in collaboration with researchers and professors from Universities and Research Institutions of four different continents (South America, North America, Europe and Asia). The book was divided in the following chapters: 1. Propagation and orchard establishment (Giacobbo et al.); 2. Traditional pear varieties in the east region of Republic of North Macedonia (Selamovska et al.); 3. An updated view on fertilization and pollination in European pears (Pyrus communis) (Goldway et al.); 4. Vegetative growth control (Pasa et al.); 5. Precocity production of pear trees grafted on high-vigor rootstocks (Almeida et al.); 6. Dormancy adaptation in pear trees grown under mild winter conditions in Brazil (Herter et al.); 7. Management techniques to increase yield of European pear trees grown in subtropical climate (Luz et al.); and 8. Water management based on precision agriculture for pears (Yamazaki and Miyakawa). Basic content and more specific and in-depth content are presented such as a series of research results and experiences on behavior and management tools to grown pear trees in subtropical climate, warmer conditions of the traditionally cultivated areas, subject of world-wide interest in the face of the climatic changes that are occurring over the years. (Imprint: Nova).